Situating the COVID-19 pandemic in the context of the Indian economy - Praveen K. Jha; Meghna Goyal (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The COVID-19 pandemic has caused a major global health crisis, the onset of which, and containment policies for, have also led to a global economic crisis. The effects of the pandemic on the economies of various countries depended on their position in the international economic hierarchy, and critically, the fiscal and monetary policy tools they employed to manage the economy. In India, we find that the pandemic and ensuing lockdown policy led to various supply chain disruptions and standstills of economic activity in most sectors such that output, employment, wages, and demand suffered a huge decline. Furthermore, our analysis shows that monetary and fiscal policy tools were largely inadequate in dealing with these big challenges to the economy. Fiscal stimulus amounted to a small percentage of the GDP and did not undertake sufficient social provisioning; and monetary policy's thrust was toward the injection of liquidity through credit provision when demand for loans was low. The policy package of the pandemic has led to an overall contraction of the Indian economy and widening income inequality. Estimations for India's economic revival are bleak and worsening with recent developments in the global economy.
Keywords: E61; F62; I18; 330; COVID-19; fiscal policy; growth; inequality; monetary policy